Review—The Physics of Recombinations in III-Nitride Emitters. (1st January 2020) - David, Aurelien; Young, Nathan G.; Lund, Cory; Craven, Michael D.
Abstract : The physics of carrier recombinations in III-nitride light emitters are reviewed, with an emphasis on experimental investigations. After a discussion of various methods of measuring recombination dynamics, important results on recombination physics are examined. The radiative rate displays a complex behavior, influenced by Coulomb interaction and carrier screening. Non-radiative recombinations at low and high current are shown to scale with the overlap of electron-hole wavefunctions, similarly to the radiative rate, leading to a compensation effect which explains the high efficiency of III-nitride emitters. Finally, the droop current is decomposed into two contributions: the well-known Auger scattering, and a defect-assisted droop process, which is shown to play an important role in the green gap.